Influence of minimally invasive cavities on color stability of dental crowns with different filling sealers - Alice Corrêa Silva-Sousa; Manoel Damião Sousa-Neto; Rafael Verardino Camargo; Thamires Diogo Lima; Antônio Castelo Branco; Fernanda de Carvalho Panzeri Pires-; André Luís Faria-; Francisco Wanderley Garcia Paula-Silva; Renato Roperto; Aline Evangelista Souza-Gabriel; Jardel Francisco Mazzi-Chaves (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract: The minimally invasive endodontic access is not directly associated with tooth discoloration in the presence of bioceramic or epoxy resin-based root canal sealers. This study aimed to evaluate the influence of minimally invasive access and endodontic sealer composition on the color stability of endodontically-treated teeth, the restorative material adaptation, and the presence of remaining filling material in the pulp chamber. Endodontic access surgery was performed in maxillary central incisors, either through conservative or minimally invasive approaches, and the root was filled with AH Plus or Bio-C Sealer. The crown color was measured with a spectrophotometer at baseline and after root obturation, restoration, and specimen storage for one year in an oven. The occurrence of voids in the restoration and the remaining filling material was analyzed using micro-CT scans. The Yellowness Index (YI) and color changes (∆E00) were calculated after each color measurement. Data of micro-CT were submitted to 2-way ANOVA, and YI and ∆E00 were analyzed with repeated-measures ANOVA. Pair-wise comparisons were performed with Tukey's test (α = 0.05). The experimental conditions had no effect on the presence of the remaining material. The minimally invasive access associated with Bio-C Sealer resulted in more voids between the restoration and the remaining filling material. Only the evaluation time affected YI and ∆E00 values. Specimens became more yellow after filling and storage in the oven (the highest ∆E00 values). The present study showed that sealer and minimally invasive cavities are not associated with crown color stability following endodontic treatment.